Local Evaluation of Variation in Pulse Wave Velocity over the Cardiac Cycle using Single-Element Ultrasound Transducer - Nabeel, P.M.; Raj Kiran, V.; Jayaraj, Joseph; Mohanasankar, Sivaprakasam (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2018)
A method and system for single-site measurement of local pulse wave velocity (PWV) and its variation over the cardiac cycle are presented. The proposed system employs a single-element ultrasound transducer and associated custom technology to record arterial diameter and wall thickness waveforms in real-time. Simultaneously acquired blood pressure, diameter and wall thickness parameters were used to evaluate diastolic local PWV (CD) and systolic local PWV (CS) from an arterial site of interest. The developed prototype system was validated on a cohort of 15 subjects (age = 43±12 years) that includes normotensives and hypertensives. CS and CD measurements were obtained from the left carotid artery. A significant difference between carotid CS and CD (AC) was observed in all recruited subjects (group average AC = 0.92±0.76 m/s), illustrating the arterial pressure dependency of local PWV. The absolute values of CS and CD were within a range of 3.39 m/s to 7.5 m/s and 3.12 m/s to 5.82 m/s respectively. Normotensive versus hypertensive group-wise analysis was performed to investigate the degree of variation in the carotid local PWV over a cardiac cycle among different BP categories. Study results demonstrated that the proposed approach has a potential to provide valuable surrogate markers for cardiovascular risk assessment.